Relationship of Knowledge to SBAR Communication Attitude During Patient Handover in Recovery Room in Anesthesiology Nursing Students of Aisyiyah University Yogyakarta - Azva, Zahara Febria; Murdiyanto, Joko; Rosidah, Istiqomah (Jurnal Kesmas Prima Indonesia, 2025)
Communication failure can lead to malpractice, misunderstanding, delayed diagnosis, service, additional costs, incomplete information, patient and family dissatisfaction and can even cause death, so effective communication with the SBAR method is needed during patient handover in the recovery room. This study aims to determine the relationship between the level of knowledge and the attitude of SBAR communication during patient handover in the recovery room in Anesthesiology Nursing students at 'Aisyiyah University of Yogyakarta. This research method uses quantitative correlation with a cross-sectional design. Sampling with random sampling totaling 67 respondents. Data were collected using a questionnaire with Spearman rank analysis. The results of the Spearman Rank correlation test obtained a p-value of 0.000 <0.005 and a correlation value of 0.758 (strong), meaning that there is a relationship between knowledge and the attitude of SBAR communication during patient handover in the recovery room in Anesthesiology Nursing students at 'Aisyiyah University of Yogyakarta. The majority of respondents had good knowledge of 35 respondents (52.5%) and good attitudes of 37 respondents (55.2%).